Radiofrequency ablation for papillary thyroid microcarcinoma with a trachea-adjacent versus trachea-distant location - Haoyu Jing; Lin Yan; Jing Xiao; Xinyang Li; Bo Jiang; Zhen Yang; Yingying Li; Bin Sun; Mingbo Zhang; Yukun Luo (International Journal of Hyperthermia)
Objective To evaluate the outcomes of radiofrequency ablation (RFA) for papillary thyroid microcarcinoma (PTMC) adjacent to the trachea and compare them with those of PTMC distant from the trachea.Methods Patients who received RFA for solitary low-risk PTMC between June 2014 and July 2020 were reviewed and classified into adjacent and distant groups. To balance between-group confounders, the propensity score matching approach was employed. Volume, volume reduction ratio (VRR), tumor disappearance, complications, and disease progression were assessed and compared between the groups. Furthermore, factors affecting disease progression were evaluated.Results A total of 122 and 470 patients were included in the adjacent and distant groups, respectively. Overall VRR was 99.5% ± 3.1 and cumulative tumor disappearance rate was 99.4% after a mean follow-up time of 40.1 months ± 16.2. Overall disease progression and complications incidence were 3.7% and 1.0%, respectively. No substantial differences were observed between the two groups in the latest volume (0.8 mm3 ± 4.1 vs. 0.9 mm3 ± 4.2, p = .77), VRR (99.7% ± 1.6 vs. 99.5% ± 2.7, p = .75), cumulative tumor disappearance rate (92.6% vs. 94.2%, p = .58), and incidence of disease progression (4.1% vs. 4.5%, p = .70) and complication (1.7% vs. 0.8%, p = .86) after 1:2 matching. Additionally, tracheal adjacency exhibited no association with disease progression in multivariate Cox regression analysis (p = .73).Conclusion For eligible patients with PTMC located adjacent to or distant from the trachea, RFA may offer a safe and effective alternative treatment method.